Evaluation of Dog Walking Programs to Promote Student Nurse Health - Morgan Yordy; Emily Graff (The Ohio State University Libraries, 2019)
Aim: To provide a brief review of health concerns associated with a sedentary lifestyle and summarize some of the benefits of walking, with specific focus on the value of dog-walking programs as a means to improve health and wellness for the student nurse. Methods: A professor within the School of Nursing and Doctor of Veterinary Medicine collaborated to review research on the benefits of dog walking and interventions utilizing dogs to increase and sustain physical activity in their owners and those that enjoy the companionship a dog can provide. Results: Dog walking is an intervention to increase activity among student nurses due to companionship and the sense of obligation dogs provide. Research suggests that dog owners are more physically active with subsequent health benefits for both owners and dogs. Animal assisted therapy programs within the university setting can link students with dogs to improve physical activity. Conclusion: Dog walking has benefits to both people and dogs. Nursing faculty can develop physical activity programs within their institution that incorporate walking a dog to enhance physical activity among student nurses. Further research is needed to empirically evaluate effectiveness of dog walking in the student nurse population.